Dinner with the President - Sumar, Sabiha; Sathananthan, Sachithanandam (Sathananthan, Sachithenandam, 2007)
Verzio FF submission Dictator, democrat, defender or dummy - what do Pakistanis really think of President Musharraf? From the middle classes to the mullahs and Musharraf himself, this insightful and timely documentary from acclaimed film-maker Sabiha Sumar explores issues of political power and human rights in Pakistan, considered geopolitically to be one of the most important, and troubled, countries in the world.